PICTURE OF GRATITUDE IN PERSONS WITH PHYSICAL DISABILITIES - Indri Srimulya; Julia Ayu Anggraini; Kasiyanti; Dinda Raihana; Muthmainnah Isnaini; Adelia Puspita; Tarisya Tridea Nanda; Nency Nabella; Cindy Giovani Yuselly; Carissa Farras Yufi; RA Miftah Cahyani; Jasmine Annisa Alnilam Cahyani; Anggi Mela Utami (Journal of Islamic Psychology and Behavioral Sciences, 2023)
Data from the Central Department of Statistics in 2022, there are around 24.6 million people with disabilities in Indonesia, divided into 17 million people with disabilities who are of productive age and 7.6 million people who are working. This study aims to find out the description of gratitude in people with physical disabilities. The selection of the sample used in this research is purposive sampling technique. This study uses a qualitative method with a phenomenological approach. The research subjects in this study were 2 persons with disabilities in the Budi Perkasa Sentra Palembang. Data collection techniques in this study are by way of interviews and observation. The results of the study showthat both subjects have a sense of gratitude in their lives. This can be seen from the attitude or nature of gratitude that the subject has, namely being grateful with his heart, words, and deeds. They do not forget to worship Allah, obey all orders and stay away from His prohibitions, and apply good words in daily life.